Design of a Collaborative Scanning System for Mobile Robots Aimed at Large-Size Components - Wen, Yu; Sun, Hongchang; Shu, Fangquan; Ma, Chenglin; Mu, Yan; Tian, Sijia (International Journal of Computer Science and Information Technology, 2026)
High-precision and full-coverage 3D scanning of large and complex components such as aerospace structures, wind turbine blades and high-speed train car bodies is an important technical demand in the development of high-end manufacturing. Traditional fixed measuring equipment is limited by its operating range, while handheld scanners suffer from low efficiency and heavy reliance on manual operation. To address these issues, this paper designs a collaborative scanning system for mobile robots oriented to large-size components. An intelligent scanning system with autonomous navigation and path optimization capabilities is developed by equipping a mobile robot platform with a six-axis robotic arm and a 3D scanner. The research focuses on hardware system integration and point cloud data processing, with emphasis on optimizing the point cloud denoising parameters based on the SOR algorithm and the point cloud registration method based on RMFD+ICP fusion. This system scheme effectively improves the automation level and data quality of 3D measurement for large-size components, and provides a theoretical basis and technical support for practical engineering applications.